Interpersonal emotion regulation and depressive symptoms in parent-adolescent dyads: a daily-diary investigation - Gadassi-Polack, Reuma; Questel, Marcia; Sened, Haran; Marshall, Hannah E.; Chen, Grace J.; Geiger, Eva J.; Bar Yosef, Tom; Joormann, Jutta (Emotion, 2025)
Deficient parental extrinsic interpersonal emotion regulation (IER, how people regulate others’ emotions) is a known risk factor for adolescent depression. Although IER and depression development are transactional, dyadic processes, previous work has almost exclusively focused on how parental IER is associated with adolescent depression. The association between parental IER and adolescent depression, and the associations between adolescent IER and adolescent and parental depression have received little attention. Moreover, most studies have focused on the regulation of negative but not positive affect. We address these gaps by examining associations between parent and adolescent IER and depressive symptoms using the actor–partner interdependence model framework. For 28 days, 112 parent–adolescent dyads (12–18-year-old adolescents) completed a dyadic daily diary, reporting their own depressive symptoms and IER strategies employed in response to dyad members’ positive and negative affect. Our results, based on 5,442 data points, show that the use of positive- and negative-affect-worsening IER is associated with more depression in the regulator (be it parent or adolescent). Surprisingly, parents’ use of more negative-affect-improving IER was associated with higher levels of their own and adolescents’ depression. Finally, adolescents’ use of positive-affect-improving IER was associated with their own decreased depression. Overall, parents (vs. adolescents) used more negative- and positive-affect-improving extrinsic IER, whereas adolescents used more positive-affect-worsening extrinsic IER. Our results highlight the importance of using dyadic designs in studying depression and IER, as well as the need to consider who is regulating, the valence of the affect regulated, and the type of strategy used. (PsycInfo Database Record (c) 2025 APA, all rights reserved)